The Use of Purple Eggplant Fruit Calyx Stem (Solanum melongena L.) as an Alternative Source of Lactase-Producing Lactic Acid Bacteria - Mike Permata Sari; Radhina, Afifa; Indriani, Narita (Biotropika: Journal of Tropical Biology, 2024)
Lactose intolerance is a condition where the body cannot digest lactose due to a deficiency of the lactase enzyme in the digestive system, leading to various health issues and indirectly increasing the risk of stunting. To prevent lactose intolerance, supplements containing the lactase enzyme or foods and drinks low in lactose, such as yoghurt, are recommended. Yoghurt production requires microorganisms capable of synthesizing the lactase enzyme, such as lactic acid bacteria (LAB). This research is an experimental study exploring the potential of purple eggplant stalks and petals (Solanum melongena L.) as a new source of LAB capable of synthesizing the lactase enzyme. The experiment began with making yoghurt from milk with added purple eggplant calyx stems as initial proof of LAB presence. Milk was chosen as the initial growth medium because it contains lactose, which acts as a substrate for the lactase enzyme found in LAB. The obtained yoghurt was then inoculated into selective media, resulting in the growth of gram-positive bacilli colonies. The lactase enzyme was isolated from LAB using the sonication method. Optimum enzyme activity was achieved at 70°C and pH 7, measuring 0.0061 U/Mg. This research concludes that purple eggplant stalks and petals contain LAB capable of synthesizing the lactase enzyme. Hopefully, this research will progress to purifying the lactase enzyme and developing lactase enzyme supplements, which can be tested as a therapy for lactose intolerance.